Enhancing the Hill Cipher with a Three-Pass Protocol Approach - Siahaan, Andysah Putera Utama; Binti Saari, Erni Marlina; Hassan, Moustafa Hussein Ali; A. Khalid, Noor Aldeen; Pane, Muhammad Akbar Syahbana (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
This paper presents the design and implementation of a cryptographic scheme that combines the Hill Cipher algorithm with the Three-Pass Protocol (TPP) using mod-256 arithmetic. The objective is to provide a secure communication mechanism without direct key exchange while adapting a classical cipher to modern digital contexts. The system employs a 2×2 key matrix where plaintext characters are mapped to their ASCII values, grouped into vectors, and transformed through matrix multiplication followed by modulo reduction. The TPP structure allows both sender and receiver to apply their private keys independently, producing layered ciphertexts before the final recovery of the plaintext. A prototype application was developed using Microsoft Visual Studio 2010 (Visual Basic) to validate the approach. The program includes input fields for plaintext, ciphertext at each stage, key matrices, and a log box that records the detailed matrix operations for transparency. Experimental results demonstrate that the original plaintext can be accurately restored after multiple encryption and decryption phases, while the intermediate ciphertexts remain random and unintelligible. The findings confirm that integrating Hill Cipher with the Three-Pass Protocol strengthens confidentiality and eliminates the need for key distribution. Beyond its security benefits, the prototype also serves as an educational tool, helping students and practitioners understand both matrix-based encryption and keyless secure communication protocols.